2010
DOI: 10.1038/hr.2010.37
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of central systolic blood pressure using an oscillometric blood pressure monitor

Abstract: Current noninvasive techniques for assessing central aortic pressure require the recording of an arterial pressure wave using a high-fidelity applanation tonometer. We therefore developed and validated a novel method to estimate the central aortic systolic pressure using an oscillometric blood pressure monitor alone. Invasive high-fidelity right brachial and central aortic pressure waves, and left-brachial pulse volume plethysmography from an oscillometric blood pressure monitor, were obtained at baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
(59 reference statements)
2
40
0
Order By: Relevance
“…20 When calibrated with invasive blood pressures, the accuracy of the ARCSolver algorithm meets the data published by Pauca et al, 13 who found a difference between directly recorded cSBP and TF-derived cSBP (from invasively recorded radial pressure waveforms) of 0.0Ϯ4.4 mm Hg. This level of accuracy has been confirmed, when radial tonometric waveforms were calibrated invasively, 21,22 but we are among the first 23 to show that brachial waveforms, acquired with a regular blood pressure cuff, can be used as well. It should be pointed out that our results were obtained against gold-standard highfidelity microtip catheters, thus avoiding potential problems associated with fluid-filled systems, particularly those related to zeroing and damping, and enabling us, because of the high frequency response, to record waveforms accurately.…”
Section: Discussionmentioning
confidence: 82%
“…20 When calibrated with invasive blood pressures, the accuracy of the ARCSolver algorithm meets the data published by Pauca et al, 13 who found a difference between directly recorded cSBP and TF-derived cSBP (from invasively recorded radial pressure waveforms) of 0.0Ϯ4.4 mm Hg. This level of accuracy has been confirmed, when radial tonometric waveforms were calibrated invasively, 21,22 but we are among the first 23 to show that brachial waveforms, acquired with a regular blood pressure cuff, can be used as well. It should be pointed out that our results were obtained against gold-standard highfidelity microtip catheters, thus avoiding potential problems associated with fluid-filled systems, particularly those related to zeroing and damping, and enabling us, because of the high frequency response, to record waveforms accurately.…”
Section: Discussionmentioning
confidence: 82%
“…A number of methods and devices are currently available for estimating central aortic systolic pressure (CASP), either directly from the second peak systolic blood pressure (SBP) corresponding to the radial pulse wave (SBP2) or using a mathematical transfer function that estimates CASP. [8][9][10] The reference device for estimating these measures is the SphygmoCor system (pulse wave analysis). 7,11 Recently, a new system has been developed that estimates derived aortic pressure using an n-point moving average method (B-Pro device s + A-pulse software).…”
Section: Introductionmentioning
confidence: 99%
“…Although the noninvasive BAP waveform is only a surrogate BAP waveform, its usefulness has been confirmed in numerous studies. [16][17][18]23 Currently, all international standards, including European Society of Hypertension International Protocol, 24 Association for the Advancement of Medical Instrumentation, 25 and British Hypertension Society, 26 require that the measurement error (mean differences against standards) of tested automatic BP monitors should surpass the minimal requirement of <5±8 mm Hg in validation studies for all BP parameters. The former number refers to systematic bias, which is the group average result for the validity evaluation, and the latter refers to random error, which suggests the scatter of the error.…”
Section: Discussionmentioning
confidence: 99%
“…The noninvasive BAP waveform was obtained at a cuff pressure of 60 mm Hg in the left arm using a commercially available oscillometric cuff-based device (VP-2000, Colin Corporation, Komaki, Japan). 17 …”
Section: Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation